Dataset of River Water Quality for Saxony, Germany, 1985-2023 - Franz Dichgans; Tobias Schulze; Olaf Büttner; Wibke Busch; Christian Schulz; Dirk Sachse; Christian Schmidt (PANGAEA, 2024)
The data set was complied and curated as part of the 0-Pollution Saxony Project with the objective to provie a comprehensive overview of available measurements on river water quality. Measurements currently stored in various databases were transferred into a uniform and consistent data structure. A total of 2,892,429 individual data points measured at 2,012 measurement sites were integrated into the data set. The spatial focus is on the Free State of Saxony, where 1,670 of the measurement sites with 1,553,733 of these data points are located. Chemical data from water samples in the Free State of Saxony were compiled from various sources. The overall dataset includes data from the following sources: Elbe River Basin Community (Flussgebietsgemeinschaft Elbe): http://www.fgg-elbe.de Small Water Bodies Monitoring (Kleingewässermonitoring - KGM): https://www.ufz.de/kgm (PANGAEA data publication: Liess, M et al. 2021) iDA - Data Portal for Saxony: Provides access to environmental data and map collections. The data originate from measurement and investigation programs of the State Agency for Environment, Agriculture and Geology, and various specialized information systems of the Free State of Saxony. (http://www.umwelt.sachsen.de/umwelt/infosysteme/ida) CheOS project: https://www.ufz.de/index.php?en=44493, which provides curated datasets based on the NORMAN EMPODAT database: https://www.norman-network.com/nds/empodat/